1999
DOI: 10.1016/s1044-0305(98)00144-5
|View full text |Cite
|
Sign up to set email alerts
|

Do charge-remote fragmentations occur under matrix-assisted laser desorption ionization post-source decompositions and matrix-assisted laser desorption ionization collisionally activated decompositions?

Abstract: The precursor ions of tetraphenylporphyrins that are substituted with fatty acids can be introduced into the gas phase by matrix-assisted laser desorption ionization (MALDI) and undergo post-source and collisionally activated decompositions (CAD) in a time-of-flight mass spectrometer. The goal of the research is to obtain a better understanding of post-source decompositions (PSD); specifically, we asked the question of whether ions undergoing PSD have sufficient energy to give charge-remote fragmentations alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Although it is generally assumed that low energy fragmentations are charge-induced, previous studies on other types of compounds have shown that chargeremote fragmentation processes do occur under MALDI-PSD conditions, e.g., [36]; this may be the case for cross-ring PSD ions observed here. Glycans were then examined by MALDI mass spectrometry under PSD and CID-MS/MS conditions.…”
Section: Resultsmentioning
confidence: 49%
“…Although it is generally assumed that low energy fragmentations are charge-induced, previous studies on other types of compounds have shown that chargeremote fragmentation processes do occur under MALDI-PSD conditions, e.g., [36]; this may be the case for cross-ring PSD ions observed here. Glycans were then examined by MALDI mass spectrometry under PSD and CID-MS/MS conditions.…”
Section: Resultsmentioning
confidence: 49%
“…This work suggests that the internal energy of the collision activated ions is within the range of 1.4 to 2.9 eV reported to be necessary for CRF [3]. These authors also noted that MALDI is not amenable to ionization of FAs [11].…”
mentioning
confidence: 64%
“…However, using the solventfree preparation method with this same mix of materials produced mass spectra of all FAs tested where the [FAϩLi] ϩ and the desired [FAϪHϩ2Li] ϩ ions dominate even the matrix ions (Figure 1). This is remarkable, especially in view of the expectation that MALDI is not suitable for producing the desired CRF ions from FAs [11]. These results demonstrate that solvent-free sample preparation is superior for this application and that taking into account ionization suppression of analyte by the matrix can lead to ionization of compound types thought not to be amenable to MALDI MS analysis.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The few studies that describe the fragmentation of tetraphenylporphyrins in the MS/MS mode [12][13][14][15][16] show that this approach gives valuable structural information about the peripheral substituents. MS/MS is expected to be useful for the chemical characterization of porphyrins because it allows a rapid identification of porphyrins in mixtures, especially those resulting from synthetic procedures.…”
mentioning
confidence: 99%